Mechanisms of change of a novel weight loss programme provided by a third sector organisation: a qualitative interview study. (December 2016) - McMahon, Naoimh; Visram, Shelina; Connell, Louise
Abstract Background There is a need for theory-driven studies that explore the underlying mechanisms of change of complex weight loss programmes. Such studies will contribute to the existing evidence-base on how these programmes work and thus inform the future development and evaluation of tailored, effective interventions to tackle overweight and obesity. This study explored the mechanisms by which a novel weight loss programme triggered change amongst participants. The programme, delivered by a third sector organisation, addressed both diet and physical activity. Over a 26 week period participants engaged in three weekly sessions (education and exercise in a large group, exercise in a small group and a one-to-one education and exercise session). Novel aspects included the intensity and duration of the programme, a competitive selection process, milestone physical challenges (e.g. working up to a 5 K and 10 K walk/run during the programme), alumni support (face-to-face and online) and family attendance at exercise sessions. Methods Data were collected through interviews with programme providers (n  = 2) and focus groups with participants (n  = 12). Discussions were audio-recorded, transcribed and analysed using NVivo10. Published behaviour change frameworks and behaviour change technique taxonomies were used to guide the coding process. Results Clients' interactions with components of the weight loss programme brought about a change in their commitment, knowledge, beliefs about capabilities and social and environmental contexts. Intervention components that generated these changes included the competitive selection process, group and online support, family involvement and overcoming milestone challenges over the 26 week programme. The mechanisms by which these components triggered change differed between participants. Conclusions There is an urgent need to establish robust interventions that can support people who are overweight and obese to achieve a healthy weight and maintain this change. Third sector organisations may be a feasible alternative to private and public sector weight loss programmes. We have presented findings from one example of a novel community-based weight loss programme and identified how the programme components resulted in change amongst the participants. Further research is needed to robustly test the effectiveness, and cost-effectiveness, of this programme.